Weekday and Survival After Cardiac Surgery—A Swedish Nationwide Cohort Study in 106 473 Patients. Issue 5 (16th May 2017) - Dalén, Magnus; Edgren, Gustaf; Ivert, Torbjörn; Holzmann, Martin J.; Sartipy, Ulrik
Abstract : Background: The purpose of this study was to investigate the association between weekday of surgery and survival following cardiac surgery. Methods and Results: In a nationwide cohort study, we included all patients who underwent cardiac surgery in 1999–2013 from the SWEDEHEART (Swedish Web‐system for Enhancement and Development of Evidence‐based care in Heart disease Evaluated According to Recommended Therapies) register. All‐cause mortality until March 2014 was obtained from national registers. The association between weekday of surgery and mortality was estimated using Cox regression, and reported as hazard ratios with 95% CI. We used the restricted mean survival time difference to estimate loss of life related to weekday of surgery. Among 106 473 patients, 25 221 (24%), 24 471 (23%), 22 977 (22%), 20 189 (19%), 9251 (8.7%), and 4364 (4.1%) underwent surgery during a Monday, Tuesday, Wednesday, Thursday, Friday, and a Saturday/Sunday, respectively. More patients were operated on urgently during Friday to Sunday, and unadjusted analyses showed higher early and late mortality in those patients. The adjusted hazard ratios (95% CI) were 1.00 (0.89–1.13), 1.00 (0.88–1.12), 1.02 (0.90–1.16), 1.17 (1.01–1.37), and 1.05 (0.86–1.29) in patients who underwent surgery during a Tuesday, Wednesday, Thursday, Friday, and Saturday/Sunday compared to a Monday, after 1 year of follow‐up conditional on 30‐day survival. In elective surgery (n=46 146), the 1‐year restricted mean survival time difference (95% CI) was −0.5 (−1.8–0.8), −0.5 (−1.9–0.8), −1.0 (−2.6–0.5), 0.02 (−2.2–2.3), and −1.2 (−6.3–3.9) days in patients who underwent surgery during a Tuesday, Wednesday, Thursday, Friday, and a Saturday/Sunday, respectively, compared to a Monday. Conclusions: We found no evidence of a clinically relevant weekday effect in patents who underwent cardiac surgery in Sweden during a 15‐year period. These data suggest that the early risk and long‐term prognosis following cardiac surgery was not affected by the weekday of surgery. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02276950.